Institutional Structures And Agrarian Relations In The Vazhuvur Veeratteswarar Temple Inscriptions. - Pradeep , G.; Raju , V. (Journal of Neonatal Surgery, 2025)
This study examines the Vazhuvur Veeratteswarar Temple inscriptions as a source for understanding institutional structures and agrarian relations in the Chola–Pandya period. The epigraphs record land grants, tax remissions, irrigation endowments, and ritual obligations, revealing the temple’s position as an economic and administrative centre within the rural order. Attention is given to the roles of brahmadeya assemblies, ur and sabha institutions, and temple functionaries in regulating cultivation, managing surplus, and redistributing resources through religious endowments. The inscriptions indicate a close linkage between political authority and sacred institutions, in which royal titles, donor identities, and revenue assignments were integrated into a structured agrarian framework. Patterns of land classification, labour obligations, and produce allocation demonstrate the presence of negotiated relationships between cultivators, local bodies, and temple management. By situating these records within the wider South Indian epigraphic tradition, the study highlights the temple not merely as a religious space but as a node of institutional governance and agrarian control. The findings contribute to the historical understanding of rural organisation, fiscal practices, and social hierarchy in medieval Tamil Nadu through inscriptional evidence...